Klagens ABC Boken Klagesangene i dens samtid og ettertid - Granerød, Gard (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
The ABCs of Complaint: The Book of Lamentations Through the Ages analyzes the biblical Book of Lamentations. Central to the book are the questions: How can we translate the Hebrew text while at the same time taking into consideration the poetic devices of the source text and insights from recent research into biblical Hebrew grammar? What are the literary forms and content of the poems? How have readers read, understood and used Lamentations over the course of its reception history? The author examines Lamentations' literary form, its religion-historical, theological and historical content, and its contexts. In addition, selected stations along Lamentations' nomadic journey through reception history are explored. The book combines historical-critical, literary and form-critical methods. The five poems of Lamentations are analyzed according to the categories orientation (being at equilibrium), disorientation (a state of being out of balance), and reorientation (a state of existence where equilibrium has been restored), inspired by Walter Brueggemann's typology of psalms. Based on a meticulous philological analysis of the Hebrew text, the author presents a new, transparent Norwegian translation. A distinctive feature of this translation is that it, in several instances, interprets the Hebrew perfect (qatal) as a so-called precative perfect ("perfect of prayer"). The ABCs of Complaint is relevant for students of theology and religion, researchers, church employees, lay people, and all who are interested in Biblical lament literature and images of God from a historical perspective on theology and religion.